2007
DOI: 10.1080/15476910701337225
|View full text |Cite
|
Sign up to set email alerts
|

Immuno- and Hepato-Toxicity of Dichloroacetic Acid in MRL+/+and B6C3F1Mice

Abstract: Dichloroacetic acid (DCA) is a by-product of chlorination that occurs in drinking water disinfected with chlorine. Metabolism of trichloroethene (TCE) also generates DCA. TCE exposure is associated with the development of autoimmune diseases, which may be induced by TCE metabolites, such as DCA. Thus, it is important to understand immunotoxic responses to DCA. We chose 2 murine models, autoimmune-prone MRL +/+ and normal B 6 C 3 F 1 mice. Both strains of mice were exposed to DCA for 12 weeks. Following DCA tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Not surprisingly, approaches using such metabolic targeting therapies are rapidly gathering momentum as promising novel treatments for cancer (reviewed in Michelakis et al, 2008;Ralph and Neuzil, 2009). Unfortunately, DCA is not specific for tumor PDH and similar doses inhibiting the tumor enzyme also decrease other metabolic pathways causing toxicity to the normal tissues as well (Cai et al, 2007).…”
Section: Inhibition Of Pdh Activity By Pyruvate Dehydrogenase Kinase mentioning
confidence: 99%
“…Not surprisingly, approaches using such metabolic targeting therapies are rapidly gathering momentum as promising novel treatments for cancer (reviewed in Michelakis et al, 2008;Ralph and Neuzil, 2009). Unfortunately, DCA is not specific for tumor PDH and similar doses inhibiting the tumor enzyme also decrease other metabolic pathways causing toxicity to the normal tissues as well (Cai et al, 2007).…”
Section: Inhibition Of Pdh Activity By Pyruvate Dehydrogenase Kinase mentioning
confidence: 99%
“…In a number of in vitro studies, DCA is reported to enhance reactive oxygen generation (ROS) generation and oxidative stress leading to cell death (Ayyanathan et al 2012;Hassoun and Ray 2003;Wong et al 2008). In exposed in vivo models, mainly rodents, DCA is reported to cause developmental- (Smith et al 1992), spermato- (Linder et al 1997), immuno-, and hepatotoxicity (Cai et al 2007;Hassoun and Dey 2008). However, concern about DCA adversity underlies on the data generated in rodents after their exposure to this chemical at doses (up to~4,000 mg/kg) thousands of times higher than those to which humans are usually exposed (Stacpoole et al 1998).…”
mentioning
confidence: 99%
“…Increased hepatocellular carcinomas were observed in male mice given DCA in drinking water [14][15][16]. The hepato-and immunotoxicity of DCA are described in [17]. Immunotoxicity was characterized as a pronounced response in this investigation.…”
Section: Introductionmentioning
confidence: 62%